AKTIVITAS KOMUNIKASI INTERPERSONAL PUSTAKAWAN DALAM MENINGKATKAN ETOS KERJA - Muhamad Bisri Mustofa; Mutiara Cahyani Putri; Siti Wuryan; Dwi Indri Rahmawati (Nusantara Journal of Information and Library Studies (N-JILS), 2021)
Interpersonal communication activities occur in various places, also in the world of libraries, how is the relationship between librarians and users and vice versa. Observations made in this paper regarding interpersonal communication activities of librarians to improve the work ethic carried out in the library environment at MTs N 2 Bandar Lampung, which include interpersonal communication activities between librarians and users, interpersonal communication between librarians and educators, interpersonal communication between librarians and educators. The head of the library with the librarian, and interpersonal communication between the librarian, the head of the library, and the principal. In addition, this study also discusses interpersonal communication in Islam. The method used in this paper is a qualitative method with descriptive analysis to see interpersonal communication activities carried out by librarians, using data collection methods by interviewing librarians in the library of MTs N 2 Bandar Lampung, observing and practicing directly by carrying out practical lectures, as well as documentation in the form of photos of research activities, besides that this writing uses the library research method obtains data from reading books. The results of this observation and research are that interpersonal communication activities that occur in the library are intertwined both between librarians and users and between librarians with one another, as well as the consequences if there is a lack of interpersonal communication that occurs in the library on the librarian’s work ethic.Keywords: interpersonal communication, work ethic, librarianABSTRAKAktivitas komunikasi interpersonal terjadi diberbagai tempat, tidak luput juga pada dunia perpustakaan, hubungan antara pustakawan dan pemustaka maupun sebaliknya. Pengamatan yang dilakukan pada tulisan ini mengenai aktivitas komunikasi interpersonal pustakawan dengan tujuan untuk meningkatkan etos kerja yang dilakukan pada lingkungan perpustakaan di MTs N 2 Bandar Lampung, yang meliputi aktivitas komunikasi interpersonal antara pustakawan dengan pemustaka; komunikasi interpersonal antara pustakawan dengan tenaga pendidik; komunikasi interpersonal antara kepala perpustakaan dengan pustakawan; dan komunikasi interpersonal antara pustakawan, kepala perpustakaan, dengan kepala sekolah. Selain itu dalam penelitian ini juga dibahas mengenai komunikasi interpersonal dalam Islam. Metode yang digunakan dalam penulisan ini adalah dengan metode kaualitatif dengan analisis deskriptif untuk melihat aktifitas komunikasi interpersonal yang dilakukan pustakawan, menggunakan metode pengumpulan data dengan cara mewawancarai secara langsung pustakawan yang ada di perpustakaan MTs N 2 Bandar Lampung, mengamati dan melakukan praktek secara langsung dengan melaksanakan kuliah praktik, serta dokumentasi berupa foto kegiatan hasil penelitian, selain itu juga penulisan ini menggunakan metode library research dan memperoleh data dari buku bacaan. Hasil dari pengamatan dan penelitian ini yaitu aktivitas komunikasi interpersonal yang terjadi di perpustakaan tersebut terjalin baik antara pustakawan dengan pemustaka maupun antara pustakawan satu dengan yang lain, serta akibat jika kurangnya komunikasi interpersonal yang terjadi di perpustakaan terhadap etos kerja pustakawan.